The Structure Of Algebraic Argumentation Of High School Students With The Toulmin Model - Putri, Debi Suci; Hartono, Yusuf; Hiltrimartin, Cecil (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2023)
Mathematical argumentation is an important skill that must be owned in the 21st century. The purpose of the research is to analyze the structure of high school students' algebraic argumentation using the Toulmin model which consists of claim, data, warrant, and backing. This study involved 35 students in the odd semester of the 2022/2023 academic year at Muhammadiyah 1 Palembang High School. The students were asked to provide algebraic argumentation in mathematical proofs related to the quadratic function theorem. The algebraic argumentation was then analyzed using the Toulmin model. The results showed that 20% of students' mathematical argumentation skills were at level 5; 57.14% of students' mathematical argumentation skills were at level 4; 20% of students' mathematical argumentation skills were at level 3; 2.86% of students' mathematical argumentation skills were at level 2; and no students were at level 1.